Numerical Analysis of Tunnel Excavation under passing the Buildings at Close Range - Le Yang, Wuqing Lai, Haiyou Peng, Liang Zhao, Yan Shuang (Design Engineering, 2020)
With the rapid development of urban rail transit, it is common to see new lines running underneath existing tunnels or dense clusters of buildings at close range. The modeling analysis of the whole area can accurately predict the deformation of the new and existing engineering bodies, and realize the "feedback" adjustment guidance for the design and construction. In this paper, the general finite element software FLAC3D is used to carry out numerical simulation of the tunnel underpassing the dense building cluster, and analyze the influence of the excavation and support of new tunnel and its auxiliary structure on the displacement of stratum and existing buildings. The results show that the maximum displacement of ground subsidence occurs on one side of the slope directly above the station during the construction of the new tunnel. However, the pile foundation displacement and inclined deformation of the close building can only meet the code requirements after the initial support and grouting reinforcement. The research results can provide some references for the design and construction of similar track engineering.